Contribuições à taxonomia do complexo Chascolytrum subaristatum (Lam.) Desv. x Chascolytrum erectum (Lam.) Desv. (Poaceae, Pooideae, Poeae, Calothecinae) - Fritzen, Amanda (2023)
Despite a general morphological distinction within the Calothecinae subtribe, the taxonomy of Chascolytrum is still challenging. The understanding of species in the genus has been hampered, mainly, by the overlapping of floral morphological characteristics, leading to different taxonomic treatments, especially when we talk about the relationship between Chascolytrum subaristatum and Chascolytrum erectum, which differ in size and color of spikelets. Molecular studies have remained controversial, where the two species have already been synonymized and later distinguished. In addition to the molecular data, it was determined that the apex of the leaves and the root structure can also help in the identification, however, due to the wide distribution of the species, it is possible that these characters suffer some environmental influence, and reproductive organs may be more stable. Therefore, the objective was to comparatively analyze aspects related to the carpel and ovule and morphometrically evaluate the floral characteristics in order to provide additional characters for a review of the limits between the two taxa. Also, it was analyzed which edaphic components can contribute to the morphological variation of individuals. For this, 15 populations from each population were gathered, in a total of four populations, two populations for each species. The inflorescences were fixed for further dissection for morphometric analysis and processed according to usual methods for microscopy. Qualitative characteristics were observed and, for the measurements, 11 quantitative characters referring to the floral structures and five axes and two areas for the carpel and ovule were determined. The vegetative organs were collected for chemical and physical analysis of the plant tissue, as well as a soil sample for each individual. It was not possible to group the populations of each species separately and, therefore, to differentiate them. All characters included from the carpel and seminal rudiment respect the variation pattern for Pooideae, except for the presence of three layers in the inner tegument in the basal portion in the region close to the chalazal end and the presence of four plant cells in the distal pole of the dorsal wall of the , which were described for the first time in the subfamily. It is assumed that the qualitative characters, previously used to differentiate the two species, such as spikelet colors, may be influenced by edaphic characteristics, as well as the characters that influence the total flower size, such as inflorescence length, lemma length and length of the glumes, and may be good population markers.